HUMAN-AI CO-TEACHING: ENHANCING PEDAGOGICAL AGENCY OF PRE-SERVICE ENGLISH TEACHERS - Ryan Purnomo; Nunung Suryati; Fadhl Mohammed Awadh Gharamah; Evi Mahsunah; Moh. Rif’attullah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
Generative AI in the education sector is quickly becoming a successful application, offering new opportunities but also challenges in teacher education, particularly within the English as a Foreign Language (EFL) context. One of the current popular technologies is ChatGPT, which has potential in assisting in teaching, reflection, and teacher professional development. However, a lack of research has focused on pre-service English teachers' perceptions of ChatGPT or how those perceptions may influence a teacher's perception of professional empowerment. An empirical qualitative research method will be used in this paper, analyzing Indonesian preservice higher education teachers' perceptions of ChatGPT in EFL teacher preparation programs, how they use ChatGPT, and how those perceptions may influence preservice teachers' perceptions of professional empowerment. Methods of research include conducting in-depth semi-structured interviews, analyzing findings through a thematic assessment. Findings also show how preservice teachers' perceptions of ChatGPT, an empowering cognitive/teaching tool, influence preservice teachers' perceptions of overall personal/professional teacher empowerment. Also identified are five increasingly interrelated perspectives of preservice teachers' perceptions of teacher empowerment, including identity, teaching competence, technological agency, teaching efficacy, and teaching innovation.